COHERENT SPEECH AS A SUBJECT OF STUDY OF PSYCHOLOGY OF LINGUISTICS AND PSYCHOLINGUISTICS (American Journal of Interdisciplinary Research and Development, 2024)
This article in psychology and linguistics studies the development of coherent speech in children with intellectual disabilities and highlights the problem of its development. It also talks about scientists who worked on coherent speech.